KEABSAHAN PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 17 TAHUN 2018 TENTANG PENDAFTARAN PERSEKUTUAN KOMANDITER, PERSEKUTUAN FIRMA, DAN PERSEKUTUAN PERDATA - Lasakar, Musa (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
Article 23 of the KUHDagang states that registration is submitted through the registration of a district court at the location of the company. In Permenkumham No. 17 of 2018 in Article 3 Paragraph (2) states that registration is submitted through the Business Entity Administration System (SABU). The problem of existence and strength binding legislation is regulated in Article 8 paragraph (1) of Law No. 12/2011, including Ministerial Regulation, does not only regulate the existence of laws and regulations based on delegation. This research using juridical method, and problem approach is Statute Approach and Conceptual Approach. The first conclusion was drawn, with the enactment of Permenkumham No. 17 of 2018 this makes CV registration easier and more regular and also this makes it easier for investors to get information about CVs that have been registered in the SABU and secondly, Problems of establishing a CV from Permenkumham No. 17 of 2018 this is the first, the establishment of a CV must order the name first before finally registering the CV in SABU. Secondly, the CV registration place is changed to the SABU. Third, the establishment of CV is required to use authentic deeds